2020
DOI: 10.21203/rs.3.rs-58122/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of peripheral blood E2F3 mRNA as a potential diagnostic biomarker in human papillary thyroid cancer

Abstract: Background: The transcription factor E2F3 plays a vital role in regulating cell cycle progression and proliferation. In addition, many reports have shown that E2F3 exerts an oncogenic role in various cancers and is a promising therapeutic target for the treatment of some human cancers. However, the value of E2F3 in the molecular diagnosis and prognosis evaluation of papillary thyroid cancer (PTC) has rarely been reported. The aim of this study was to evaluate the clinical significance of E2F3 in the early diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Moreover, E2F3 could form a dimer with cyclin D1 and participate in the regulation of the cell cycle, which is related to a variety of oncogenic and tumor suppressor genes. 24 In 2020, Zhao et al, 25 referred that the peripheral blood E2F3 could be regarded as a potential diagnostic biomarker for PTC. Vormbrock et al, 26 also confirmed that the absence of E2F3 promoted the development of medullary thyroid carcinomas (MTCs).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, E2F3 could form a dimer with cyclin D1 and participate in the regulation of the cell cycle, which is related to a variety of oncogenic and tumor suppressor genes. 24 In 2020, Zhao et al, 25 referred that the peripheral blood E2F3 could be regarded as a potential diagnostic biomarker for PTC. Vormbrock et al, 26 also confirmed that the absence of E2F3 promoted the development of medullary thyroid carcinomas (MTCs).…”
Section: Discussionmentioning
confidence: 99%